Adolescent Alcohol Consumption: The Role of Peer Influence, Social Media, and Policy Interventions - Batara, Andi Surahman Batara (Journal of Health Literacy and Qualitative Research, 2022)
Adolescent alcohol consumption remains a critical public health concern, influenced by peer dynamics, social media exposure, and socioeconomic factors. This study examines the role of these variables in shaping adolescent drinking behaviors and explores the effectiveness of regulatory policies in mitigating alcohol-related risks. A systematic literature review was conducted, analyzing studies from PubMed, Psyc, Scopus, and other academic databases. Findings reveal that peer influence significantly contributes to adolescent alcohol use, while social media platforms act as both a risk factor and a potential tool for intervention. Cross-national comparisons highlight the effectiveness of strict alcohol regulations, such as higher taxation and sales restrictions, in reducing underage drinking rates. Furthermore, socioeconomic disparities impact adolescent exposure to alcohol marketing and accessibility, necessitating targeted policy interventions. The study underscores the urgent need for comprehensive policies addressing both environmental and social determinants of adolescent alcohol use. Strategies should include stricter advertising regulations, digital health interventions, and community-based prevention programs. Future research should focus on longitudinal studies assessing the long-term effects of adolescent alcohol consumption, as well as innovative intervention methods leveraging social media platforms. By addressing these gaps, policymakers and public health professionals can develop more effective strategies to mitigate adolescent drinking behaviors and reduce long-term health risks.